Socio-ecological significance of urban green space under a changing climate: Perspectives and concerns of young adults in Germany - Kwadwo Yeboah BOTAH (Present Environment and Sustainable Development)
In the context of accelerated urbanization and climate change, urban green spaces (UGS) are highly considered an essential pillar of a livable city that promotes a healthier environment and enhances human socio-ecological needs. In this light, several studies have examined public perceptions of the health effects of UGS for informed urban planning. This study supports this field by employing a web-based questionnaire survey to explore the perspectives of young adults in Germany on the health potentials of UGS, their climate change impact awareness as well as any existing concerns as they utilize these spaces, particularly in the context of climate change. The results show that young adults in Germany irrespective of their level of concern and awareness of climate change impacts overwhelmingly recognize and appreciate the positive health and well-being impacts of UGS and their growing importance in the context of climate change. In general, higher affinity was placed on the mental health benefits of UGS, however under climate change conditions, greater affinity was given to ecological benefits. Likewise, UGS's role in temperature regulation was perceived as the most increasingly important now and under climate change conditions. However, poor cleanliness, safety, security, and noise were major concerns. Several demographic factors that influenced respondents' awareness, perceptions, and concerns were revealed. Ultimately, the study concludes that UGSs are highly valued but a segment of the population lacks awareness of or underestimates its health effects. Hence, it echoes the critical need for extensive public education on climate change impacts and the health benefits of UGS while also emphasizing the importance of incorporating the perspectives and concerns of young residents into the planning and design of these spaces to advance their sustainability, resilience, and multifunctionality in the face of climate change.